Impact sensitivities of energetic materials derived from easy-to-compute ab initio rate constants. Issue 15 (29th March 2023) - Claveau, Romain; Glorian, Julien; Mathieu, Didier
Abstract : Impact sensitivities of energetic materials are correlated to ab intio rate constants, resulting in a practical method to estimate the drop weight impact height. Abstract : New procedures to estimate the impact sensitivity of energetic materials are derived from an earlier semiempirical model correlating the drop weight impact height h 50 to the rate constant k for the propagation of the decomposition process, assumed to be the limiting step. The new models are obtained by removing step by step the empiricism in the evaluation of k . We end up with a full ab initio expression for this constant in terms of theoretical activation energies and prefactors. The resulting model casts doubt on a previously introduced assumption regarding the temperature at the reaction front. Moreover, it questions possible interpretations of semiempirical estimates. A systematic comparison against alternative methods shows that although somewhat less accurate than its earlier semiempirical version, this ab initio model shows a predictive value similar to heavily parameterized approaches. The results imply that the decomposition kinetics accounts for at least 50% of the variation in the logarithms of drop height data.